Factors That Influence The Interest In Using Tax Consultant Services - Rina Hartanti; Muhammad Nuryatno (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2019)
The aim of the study is to examine the effect of tax sanction assertivenessfactors, knowledge oftaxation, taxpayer motivation, and the tax authorities’ service quality on the interest in using tax consultant services. Data was obtained by distributing 200 questionnaires to all personal taxpayers located in the working area in DKI as respondents and only 192 questionnaires were successfully filled out and returned, hence, analyzed using Structural Equation Models (SEM). The result of the study showed: (1)Tax sanction assertiveness does not affect the interest of taxpayers in using tax consultant services. (2) Knowledge of taxation has apositive and significant effect on the interest in using tax consultant services. (3) Motivation of taxpayers has a positive and significant effect on the interest in using tax consultant services. (4) Tax authorities’ servicequality does not affect the interest in using tax consultant services.